Nilai Pendidikan Akhlak dalam Al-Quran (Studi atas Kisah Nabi Yusuf dan Korelasinya dengan Kasus di Indonesia): Nilai Pendidikan Akhlak dalam Al-Quran (Studi atas Kisah Nabi Yusuf dan Korelasinya dengan Kasus di Indonesia) - Kardiyanto, Wawan (ISEDU : Islamic Education Journal, 2023)
The story of Prophet Yusuf As, the best story in the Qur'an or in the word of Allah called ahsanal Qashashi, is the best and most beautiful true story of all time. The example of Prophet Yusuf As through divine revelation to Prophet Muhammad SAW is not a made-up story. This research aims to find out the character education values contained in the story of Prophet Yusuf As which contains Islamic values in accordance with human nature for mental and spiritual education. Most people recognize the Prophet Yusuf As only because of his good looks and beauty but in fact the Prophet Yusuf As has more than that because he has beautiful and noble morals. Allah praised him as a person who always does good. Applying the noble morals possessed by the prophets is part of piety and devotion to Allah. The method used in this article is library research to understand and study theories from various literatures relevant to the research. Providing the necessary equipment, organizing time, and reading or recording research materials are the four stages of library study in research. The results of this study indicate the values contained in the story of Yusuf, which make learning for mankind in berakhul karimah, namely; The values of courtesy to elders, mutual openness and compassion for parents and siblings, patience and forgiveness, and the Prophet Yusuf is an intelligent (fathanah), trustworthy (amanah), honest (Siddiq), convey (tablig).